Effectiveness of an e-portfolio-based writing method using analytic traits on writing performance of EFL students - Azarfam, Aliasghar Yousefi; Abd. Samad, Arshad; Noordin, Nooreen; Omar, Zoharah; Mohamed Razali, Abu Bakar (Human Resource Management Academic Research Society, 2017)
The major focus of this study was on the effect of an alternative method of writing instruction on the writing ability of Iranian university students in a public Malaysian university. The writing method introduced and implemented in this study was developed based on the four dimensions of process, genre, electronic portfolios, and analytic traits of writing. The data were sequentially collected by collecting the major and prior quantitative data through conducting an experimental study. The selected sample for the study was randomly assigned to two Experimental Groups and one Control Group. The first treatment group (WE1) incorporated the use of an on-line e-portfolio system with the analytic traits of writing while the second (WE2) only used the on-line system. The results of the research showed that although the observed difference between the two treatment groups was not significant, the learners in WE1 expressed a difference in the attitudes towards the use of analytic traits of writing. Both groups, however, showed a significant difference when compared to the performance of students in the control group. Multiple Analysis of Variance (MANOVA) also showed significant differences between both WE1 and WE2 compared to the control group in performance on the five traits of writing (Content, Organisation, Vocabulary, Language Use, and Mechanics). Although the learners in WE1 were expected to have higher writing performance compared to WE2 due to their exposure to the analytic traits of writing, this outcome was not observed. Nevertheless, the respondents of WE1 expressed satisfaction with the learning strategies they learned and applied in the course. From a teaching perspective, it was found very crucial to scaffold the writers and provide them with a framework and a pattern to know what to do and how to cover the different stages of writing.